2012
DOI: 10.1002/crat.201200200
|View full text |Cite
|
Sign up to set email alerts
|

Brittleness of protein crystals

Abstract: A simple technique for studying the brittleness of small crystals is reported. The limits of fracture toughness of tetragonal hen‐egg white lysozyme crystals, oriented with their c‐axis normally to the substrate, were measured. The strong mechanics anisotropy of those crystals was confirmed. The role of the water present in the protein crystal lattice was re‐considered in seek for a more holistic understanding of the process, the idea being that the intra‐crystalline solution sustains the globular protein mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The plastic characteristics for glucose isomerase (GI), ferritin, trypsin, and insulin crystals besides HEWL ones have been also investigated by indentation method [33] and pushing method with a glass filament [34,35]. The unique plastic behavior such as creep was observed for GI crystals [33].…”
Section: Introductionmentioning
confidence: 99%
“…The plastic characteristics for glucose isomerase (GI), ferritin, trypsin, and insulin crystals besides HEWL ones have been also investigated by indentation method [33] and pushing method with a glass filament [34,35]. The unique plastic behavior such as creep was observed for GI crystals [33].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the crystals exhibited significant solvent content of 65% [4]. Nanev reported that intra-crystalline water works as a "lattice glue" and helps to hold the crystal structure together [59]. This effect is based on the dynamic hydrogen bond chains that form between some intra-crystalline water molecules, which are likely to become elongated to connect the amino-acid residues of adjacent protein molecules in the crystal lattice [59].…”
Section: Anisotropic Behavior Of Native Hheg Crystalsmentioning
confidence: 99%
“…Nanev reported that intra-crystalline water works as a "lattice glue" and helps to hold the crystal structure together [59]. This effect is based on the dynamic hydrogen bond chains that form between some intra-crystalline water molecules, which are likely to become elongated to connect the amino-acid residues of adjacent protein molecules in the crystal lattice [59]. This effect is expected to be observed within very small channels and gaps where the molecules are at an appropriate distance to each other to be connected.…”
Section: Anisotropic Behavior Of Native Hheg Crystalsmentioning
confidence: 99%
“…It has been known for a long time that the disordered solvent phase fills the void between molecules in the protein crystal lattice [16]. The role of water included in protein crystals acting like an 'additional glue' to hold protein molecules together has been considered elsewhere [17] and is not within the scope of this paper.…”
Section: Thermodynamic Basis Of Ebde and Definition Of Protein-to-watmentioning
confidence: 99%